Approach for distributed BPEL engine placement using K-means - Rong-heng LIN; Bu-dan WU; Yao ZHAO; Fang-chun YANG (Tongxin xuebao)
Aiming to solve the distributed BPEL engine placing problem in cloud, a K-means based distributed BPEL en-gine placing algorithm was proposed. The algorithm transforms the BPEL engine placing model into some optimization model in mathematics, and the optimization problem is solved by K-means algorithm. How to apply the algorithm in dif-ferent network topologies was also discussed, such as random graph and tree network. In the end, statistical software R was used as experiment tool to evaluate the algorithm. Results show that the proposed method can provide a more opti-mized bandwidth usage of combined BPEL service execution.